Argumentação e força no Héracles de Eurípides - Barbosa, Tereza Virgínia Ribeiro (Organon, 2012)
The myth of Heracles from its beginning is connected with an history of physical struggle andsuccess reached by ‘bia’. In the present article I analyse how Euripides presents in the ‘Heracles’ thisconcept and how he provokes controversy about this ‘ancient valour’. Dramatically the poet exposes ‘bia’and the advantages and the prejudices of incorporate this concept in our ordinary ‘praxis’. In the end of theplay Euripides seems to suggest the necessity to making a crucial choice between ‘bia’ and ‘peithó’ as if‘peithó’ could be one of the manners to control this instinct inside us.